VORTEX ELEMENT METHOD SIMULATION OF KNOTTED VORTEX FILAMENTS EVOLUTION - S. A. Dergachev; G. A. Shcheglov (Научный вестник МГТУ ГА, 2016)
Research paper is devoted to the description of a new modification of the algorithm for calculating the vortex filaments motion. The results of methodological studies showing that this algorithm can correctly simulate the elongation, shortening, bending and reconnection of vortex filaments, as well as known qualitative phenomena arising from the vortex rings interaction are given. Particular attention is paid to the repetition of the calculation recently investigated experimentally the evolution of bound vortices. It is shown that with the developed algorithm can be steadily modeled complex vortex loops evolution. The main advantage of the new algorithm is stability and high-speed computing.